2011
DOI: 10.1378/chest.10-0163
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exhaled Breath Condensate pH in a Large Population With Asthma

Abstract: Asthma is a complex syndrome. Subjects who are not experiencing an exacerbation but have low EBC pH appear to be a unique subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 39 publications
5
39
0
Order By: Relevance
“…In acute asthma, acidification of EBC has been reported by several independent investigators [9,31,32,33]. These changes in EBC pH have also been observed in pediatric populations [10,34,35,36,37].…”
Section: Discussionmentioning
confidence: 66%
“…In acute asthma, acidification of EBC has been reported by several independent investigators [9,31,32,33]. These changes in EBC pH have also been observed in pediatric populations [10,34,35,36,37].…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, as BMI increases in subjects with asthma, a reduced L-arginine/ADMA results in greater airway epithelial iNOS uncoupling. This may explain why several studies have found lower FE NO levels in obese subjects with asthma and potentially why higher BMI has been associated with greater airway oxidative stress (1)(2)(3)(4). This mechanism may be potentially constrained to the airways, as biomarkers of systemic oxidative stress have been found not to explain the obesity-asthma association (24).…”
Section: Discussionmentioning
confidence: 99%
“…Although adiposity imposes an important load on the respiratory system, beyond worsening dyspnea, there is little evidence that obesity affects asthma by increasing traditional biomarkers of airway inflammation or bronchial hyperresponsiveness. In fact, increasing body mass index (BMI) has been paradoxically associated with reduced levels of fractional exhaled nitric oxide (FE NO ) and sputum eosinophils (1)(2)(3)(4). In addition, cluster analyses identify obesity as part of a phenotype characterized by less atopy and adult-onset asthma, with additional analyses suggesting obesity may be causally related to asthma among those with adult-onset asthma with less atopy (5,6).…”
mentioning
confidence: 99%
“…Hunt et al showed that pharyngeal acidification leads to decreased EBC pH within 15 min and proton-pump inhibitor (PPI)-responder chronic cough patients had lower EBC pH values [30]. In COPD patients [31] and in a large cohort of asthmatic subjects [32] reduced EBC pH was associated with GORD. In spite of the lack of difference in condensate pH between asthmatic patients with and without GORD in another study, EBC pH was increased in the GORD group after PPI treatment [33].…”
Section: Discussionmentioning
confidence: 99%